ICT-Based Lajur Bata Game Media Using Guided Discovery Method on Flat-sided Space Geometry Subject - Lucky Stiardi Rionanda; Farida Farida; Fredi Ganda Putra; Erfina Damayanti; Kenny Candra Pradana (CV. Tripe Konsultan, 2022)
This study aims to develop an interactive medium based on ICT with the Guided Discovery method for the Lajur Bata game on the geometry of the flat side space. In this study using research and development procedures through ADDIE model with the following stages: 1) Analysis; 2) Design; 3) Development; 4) Implementation; 5) Evaluation. The Feasibility Test involved 3 Material Experts and 3 Media Experts, while the Attractiveness Test involved 10 students in the Small Scale Trial, and 26 students in the Large Scale Trial. Based on the results of the validation questionnaire, both material experts and media experts have met the